Optimizing anion storage performances of graphite/ non-graphitic carbon composites as cathodes for dual-ion batteries. (10th February 2023) - Ghosh, Shuvajit; MP, Nihad; Muduli, Sadananda; Bhowmik, Subhajit; Martha, Surendra K.
Highlights: Insights into the anion storage of graphite/ non-graphitic carbon composite. Role of surface functional groups and doped heteroatoms of non-graphitic carbon. Revealing the maximum lifetime of dual-ion cells. Optimizing maximum active material loading for balanced energy-power output. Fabricating pouch type dual carbon full cell. Abstract: Anion intercalation capacity of graphite cathode is a limiting factor towards the development of dual-ion energy storage devices. A large portion of electrochemically active sites in graphite lattice remains inaccessible to anions due to the instability of electrolytes beyond 5 V. Strategy to composite graphitic intercalation along with surface storage from non-graphitic carbons to enhance capacity is explored in this work. Optimizations are performed to determine the best ratio of graphitic and non-graphitic carbons, and to find out the blend of physical properties of non-graphitic carbons that aid the surface contribution to the greatest extent. Besides, it is also optimized to obtain the maximum achievable lifetime and efficiency, suitable active material loading for balancing energy-power output, and the safest upper cut-off voltage for trading off capacity against cycle life. Surface area, pore size, functional groups, and doped elements govern the electrochemical properties of non-graphitic carbons. A composite of graphite with high surface area carbon (2477 m 2 g   −   1 ) in a 75:25 ratio doubles the capacity, whereas the composite of graphite and reduced graphene oxide at the same ratio yields prolonged cycle life at 100 mA g   −   1 within 2.0–5.0 V. The capacity improvement is invariably reproducible in dual carbon cell using composite materials as both electrodes. Graphical abstract: Image, graphical abstract